Vagotomy Affects the Development of Oral Tolerance and Increases Susceptibility to Develop Colitis Independently of α-7 Nicotinic Receptor - Martina Di Giovangiulio; Goele Bosmans; Elisa Meroni; Nathalie Stakenborg; Morgane Florens; Giovanna Farro; Pedro J Gomez-Pinilla; Gianluca Matteoli; Guy E Boeckxstaens (BMC, 2016)
Abstract Vagotomy (VGX) increases the susceptibility to develop colitis suggesting a crucial role for the cholinergic anti-inflammatory pathway in the regulation of the immune responses. Since oral tolerance and the generation of regulatory T cells (Tregs) are crucial to preserve mucosal immune homeostasis, we studied the effect of vagotomy and the involvement of α7 nicotinic receptors (α7nAChR) at the steady state and during colitis. Therefore, the development of both oral tolerance and colitis (induced by dextran sulfate sodium (DSS) or via T cell transfer) was studied in vagotomized mice and in α7nAChR−/− mice. VGX, but not α7nAChR deficiency, prevented oral tolerance establishment. This effect was associated with reduced Treg conversion in the lamina propria and mesenteric lymphnodes. To the same extent, vagotomized mice, but not α7nAChR−/− mice, developed a more severe DSS colitis compared with control mice treated with DSS, associated with a decreased number of colonic Tregs. However, neither VGX nor absence of α7nAChR in recipient mice affected colitis development in the T cell transfer model. In line, deficiency of α7nAChR exclusively in T cells did not influence the development of colitis induced by T cell transfer. Our results indicate a key role for the vagal intestinal innervation in the development of oral tolerance and colitis, most likely by modulating induction of Tregs independently of α7nAChR.